Proceedings of the 2013 ACM International Joint Conference on Pervasive and Ubiquitous Computing 2013
DOI: 10.1145/2493432.2493459
|View full text |Cite
|
Sign up to set email alerts
|

A model for WLAN signal attenuation of the human body

Abstract: Fingerprinting-based indoor localization involves building a signal strength radio map. This map is usually built manually by a person holding the mapping device, which results in orientation-dependent fingerprints due to signal attenuation by the human body. To offset this distortion, fingerprints are typically collected for multiple orientations, but this requires a high effort for large localization areas. In this paper, we propose an approach to reduce the mapping effort by modeling the WLAN signal attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
(24 reference statements)
0
22
0
Order By: Relevance
“…[10] quantifies these findings: when a person is standing 1m away from an access point facing the device, the RSSI of the WiFi signal drops over 40 dBm when receiving the signal behind that person compared to receiving it in front of it. In a distance of 10m however, there is no noticeable difference anymore.…”
Section: E the Effect Of Dense Crowdsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] quantifies these findings: when a person is standing 1m away from an access point facing the device, the RSSI of the WiFi signal drops over 40 dBm when receiving the signal behind that person compared to receiving it in front of it. In a distance of 10m however, there is no noticeable difference anymore.…”
Section: E the Effect Of Dense Crowdsmentioning
confidence: 99%
“…Fet et al presented a model for WiFi signal attenuation of the human body [10] in 20l3. Since our scenario usually in volves large (and mostly dense) crowds of people, we consider their findings within our system performance parameters.…”
Section: Related Workmentioning
confidence: 99%
“…The obstacle we study is specific to human body blocking effect as mobile devices are carried by people. Existing work [9]- [12] has observed that human body has a significant impact on WiFi signals (in both 2.4 GHz and 5 GHz frequencies). Since Bluetooth also uses 2.4 GHz frequency, we infer that similar obstacle effect of human body on WiFi signals is also applicable to Bluetooth signals.…”
Section: A Path Loss Effects On Bluetooth Signalsmentioning
confidence: 99%
“…When the channels are considered separately, small fluctuations are visible in each, however these are lost when considering them in aggregate. There are a variety of studies that investigate the effect of human bodies on fingerprinting-based and range-based positioning [10][11][12]. Early work approximated the attenuation due to body shadowing with a Rician distribution [10].…”
Section: Introductionmentioning
confidence: 99%